Green national accounting with a changing population - Geir B. Asheim (University of Oslo, Department of Economics, 2003)
Following Arrow et al. (2003), this paper considers green national accounting when population is changing and instantaneous well-being depends not only on per capita consumption, but also population size. It is shown that welfare improvement can be indicated by an expanded “genuine savings indicator”, which also takes into account the total value of population growth, or by an expanded measure of real NNP growth. Practical ways of approximating these measured are discussed. By assuming constant returns to scale, the measures can be related to the value of per capita stock changes and per capita NNP growth, using a result due to Arrow et al. (2003). The result are compared to those arising when instantaneous well-being depends only on per capita consumption, and not on population size.
Keywords: D60; D90; O47; Q01; 330; National accounting; Population; Dynamic welfare; Sustainability; Ökosozialprodukt; Bevölkerungsentwicklung; Dynamisches Modell; Nachhaltige Entwicklung